PENGEMBANGAN KREATIVITAS SENI BUDAYA PESERTA DIDIK MELALUI PEMBELAJARAN TARI DAN MUSIK BAPENTAEH DI SEKOLAH DASAR - Nessa Mezhila Akrima; Maihelya Agrini; Helisa Nia Anjani; Alya Rahma Dhani (Jurnal Tunas Pendidikan, 2024)
This research aims to examine the process of developing students' artistic and cultural creativity through learning bapentaeh dance and music in elementary schools. The research method used in this research is a descriptive approach, which will examine and describe the learning of bapentaeh dance and music as an effort to develop students' artistic and cultural creativity in elementary schools. The subjects in this research focused on students of SDN 34/I Teratai who were involved in learning bapentaeh dance and music. The results of this research show that students and girls have great potential in developing artistic and cultural creativity through learning bapentaeh dance and music.